Sprinting to the top: comparing quality of distance variety and specialization between swimmers and runners - Born, D.-P.; Romann, M.; Lorentzen, J.; Zumbach, D.; Feldmann, A.; Ruiz-Navarro, J. J. (Frontiers in Sports and Active Living, 2024)
Objectives To compare performance progression and variety in race distances of comparable lengths (timewise) between pool swimming and track running. Quality of within-sport variety was determined as the performance differences between individual athletes' main and secondary race distances across (top-) elite and (highly-) trained swimmers and runners.